If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -6) + -9 = 19 + -6x Reorder the terms: 2(-6 + x) + -9 = 19 + -6x (-6 * 2 + x * 2) + -9 = 19 + -6x (-12 + 2x) + -9 = 19 + -6x Reorder the terms: -12 + -9 + 2x = 19 + -6x Combine like terms: -12 + -9 = -21 -21 + 2x = 19 + -6x Solving -21 + 2x = 19 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -21 + 2x + 6x = 19 + -6x + 6x Combine like terms: 2x + 6x = 8x -21 + 8x = 19 + -6x + 6x Combine like terms: -6x + 6x = 0 -21 + 8x = 19 + 0 -21 + 8x = 19 Add '21' to each side of the equation. -21 + 21 + 8x = 19 + 21 Combine like terms: -21 + 21 = 0 0 + 8x = 19 + 21 8x = 19 + 21 Combine like terms: 19 + 21 = 40 8x = 40 Divide each side by '8'. x = 5 Simplifying x = 5
| 10+.3x=x-2 | | 48-2x=8x+8 | | 10+1.3x=x-2 | | 42975-125m=45000-350m | | 0.3t+-0.3t=x | | 5(2-4t)+3t=5t+7 | | 0.37(28+62.7x)=56.758 | | 11+m=9 | | 5.6x^2+40x+400=0 | | 9007-5667=x | | -2y-1(3y-9)=7+9(-3-y) | | X+7x+4=172 | | -3x=-32x+151 | | x^2-mx=32 | | 1x+5(-5)=-23 | | 7x+0=4 | | 7x+0=4 | | 7-m=m+4 | | 4x(4-5)= | | 3=23-f | | 8=b-5 | | 8(-4x+16)= | | 9s+9=-45 | | 2.3=p-0.6 | | 8(-4+16)= | | 8x+80=344 | | -7.95+X=14.95 | | 42=31-7(5-4w) | | K+(-8)=11 | | Log(6)(3x+8)=4 | | 82.5-2.25+2x=338.5 | | 2x+8=sqrt(x+4) |